Community partnership program for Marinsow village’s homestay marketing in North Minahasa regency - Jefrey I. Kindangen; Heilbert A. Mapaly; Johansen C. Mandey (VIVABIO: Jurnal Pengabdian Multidisiplin, 2022)
Marinsow village is located in East Likupang District, North Minahasa Regency, North Sulawesi Province is one of the villages included in the Manado-Likupang National Tourism Strategic Area (KSPN) as well as a Tourism Special Economic Zone. The Ministry of PUPR has carried out a program to improve the quality of independent houses that support the construction of homestays and other tourist service facilities in this village, namely the construction of 62 homestays. Marinsow village has the potential of a beach tourism area. The construction of homestays and culinary services in Marinsow village took place in fiscal year 2020, and has been operating since 2021, its use as an effort to empower the community's economy. District and provincial governments are asked to be involved in the sustainability of the program to provide supporting infrastructure, as well as universities are expected to make a real contribution. The problems faced by the community are the readiness of the community to serve guests well, the problem of structuring the area, and the modern marketing of the homestay. To prepare the community group of homestay owners and of course also the tourist area, counseling and training related to marketing through electronic media is carried out, which is a proposed strategy. prepare the community group of homestay owners and of course also the tourist area, counseling and training related to marketing through electronic media is carried out, which is the proposed strategy. This is a proposed solution where it is hoped that the community and local government can improve their knowledge and skills in business management, arranging tourist areas and marketing modernly tourist huts and their beach tourism potential.